The Dimensions of Health Vulnerabilities Among Transgender People in Brazil: An Integrative Review (Revista Iberoamericana de Bioética, 2025)
Vulnerability is a central theme in public health and bioethics, and transgender people are among the populations most exposed to health risks in Brazil. This group faces high rates of sexually transmitted infections, suicidality, psychoactive substance use, violence, and experiences of social and institutional exclusion. The aim of this study was to analyze the dimensions of vulnerability and their potential mitigating factors in the health of transgender people in Brazil. An integrative review was conducted in national and international databases, following PRISMA guidelines, which resulted in the inclusion of 16 articles. The findings were organized according to Ayres’ model, encompassing individual, social, and programmatic dimensions. Results showed that vulnerabilities are interconnected, reproducing structural inequalities and barriers to access in health services, education, and employment. The conclusion drawn is that the multidimensional approach to vulnerability can guide public policies that are sensitive to the specificities of transgender populations, expanding equality, access, and effectiveness.
Keywords: transgender persons; health vulnerability; bioethics; health inequalities; public health